SOCIAL PHOBIA: PERSONALITY TYPE AND PSYCHOLOGICAL ISSUES - Babayeva, Elnara (Health and Society, 2025)
Social phobia is a widespread psychological condition, particularly prevalent in young people, where individuals experience overwhelming anxiety in social situations, leading to avoidance of social interactions and significant emotional distress. This article explores the relationship between social phobia and personality traits, with an emphasis on how specific personality types predispose individuals to develop social phobia and how these traits affect emotional well-being. The research outlines the key causes of social phobia, its emotional and behavioral consequences, and treatment strategies that can help alleviate the condition.